Efforts to Preserve Traditional Dances Through Cultural Saturday Activities at SMKN 2 Mataram - Ajeng Galuh Putri Anjani; Fatia Eliza; Khaerul Habi; Mardiatul Jannah; Mawaddah Islamiyah; Sawaludin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Traditional dance is one form of Indonesian cultural wealth that must be passed down from generation to generation (Lail & Widad, 2015). However, along with the development of the era and the increasingly rapid flow of globalization, the existence of traditional dances is often marginalized and begins to be replaced by the influence of more modern foreign cultures. In order to prevent the threat of extinction of traditional culture, SMKN 2 Mataram held a Saturday Culture activity as one of the programs to introduce, teach, and preserve traditional dances to students. However, although this activity is carried out routinely every month, various challenges are still faced in efforts to preserve traditional dances at SMKN 2 Mataram. Therefore, efforts to increase the effectiveness of Saturday Culture activities in preserving traditional dances require serious attention from various parties. Collaboration is needed between teachers, students, and schools to overcome existing problems, as well as create a school environment that supports the preservation of traditional culture through more innovative and interesting activities for the younger generation. The method used in this study is to use a descriptive qualitative research method and the data collection techniques used are observation, interviews, and documentation.